2023
DOI: 10.3390/molecules28020911
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Assembly of Fluorophores inside a Nanoliposome

Abstract: Cellular compartmentalization plays an essential role in organizing the complex and multiple biochemical reactions in the cell. An artificial compartment would provide powerful strategies to develop new biochemical tools for material production and diagnosis, but it is still a great challenge to synthesize the compartments that encapsulate materials of interest while controlling their accurate locations, numbers, and stoichiometry. In this study, we evaluated chemical characteristics of a liposome-encapsulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The estimated pK a value was shifted to the basic side compared to free CF (pK a = 6.5) due to the destabilization of the dianionic form of CF by the negative charge of the DNA phosphate backbone of WS, which is consistent with that of CF on a DNA nanostructure as reported previously. [32,39] The result indicated that the fluorescence emission of CF on naked-WS retained its sensitivity to pH changes and was effectively decreased at pH 6.0. Fluorescence microscopy analyses of naked-WS were carried out by changing the pH of the outer buffer (Figure 4a and S9).…”
Section: Characterization Of the Artificial Compartment By Fluorescen...mentioning
confidence: 93%
See 4 more Smart Citations
“…The estimated pK a value was shifted to the basic side compared to free CF (pK a = 6.5) due to the destabilization of the dianionic form of CF by the negative charge of the DNA phosphate backbone of WS, which is consistent with that of CF on a DNA nanostructure as reported previously. [32,39] The result indicated that the fluorescence emission of CF on naked-WS retained its sensitivity to pH changes and was effectively decreased at pH 6.0. Fluorescence microscopy analyses of naked-WS were carried out by changing the pH of the outer buffer (Figure 4a and S9).…”
Section: Characterization Of the Artificial Compartment By Fluorescen...mentioning
confidence: 93%
“…190 μL of the recovered solution was mixed with 110 μL of 54 % iodixanol in 1× hydration buffer and placed at the bottom of a centrifuge tube (11×34 mm, Beckman Coulter Inc.). Six additional layers of 0 to 18 % iodixanol solution [29,32] in buffer were added to the centrifuge tube (Figure S6). The tube was spun in an MLA-130 rotor (Beckman Coulter Inc.) at 150,000 × g at 4 °C for 5 h, and the fractions (55 μL per fraction) were collected.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations